Living in a Foster Home: The Single Subpolar Flagellum Fla1 of Rhodobacter sphaeroides - Laura Camarena; Georges Dreyfus (Biomolecules, 2020)
Rhodobacter sphaeroides is an α-proteobacterium that has the particularity of having two functional flagellar systems used for swimming. Under the growth conditions commonly used in the laboratory, a single subpolar flagellum that traverses the cell membrane, is assembled on the surface. This flagellum has been named Fla1. Phylogenetic analyses have suggested that this flagellar genetic system was acquired from an ancient γ-proteobacterium. It has been shown that this flagellum has components homologous to those present in other γ-proteobacteria such as the H-ring characteristic of the Vibrio species. Other features of this flagellum such as a straight hook, and a prominent HAP region have been studied and the molecular basis underlying these features has been revealed. It has also been shown that FliL, and the protein MotF, mainly found in several species of the family Rhodobacteraceae, contribute to remodel the amphipathic region of MotB, known as the plug, in order to allow flagellar rotation. In the absence of the plug region of MotB, FliL and MotF are dispensable. In this review we have covered the most relevant aspects of the Fla1 flagellum of this remarkable photosynthetic bacterium.